IDENTIFIKASI KARAKTERISTIK MEKANIS BANTALAN LUNCUR MOTOR STARTER DARI SERBUK TEMBAGA ALUMUNIUM - rizal, syamsul; suhandi, amin (Jurnal Sains dan Teknologi Indonesia, 2010)
There are many attempts to support the development of industry in Indonesia, especially on automotive sector, one of them is by replacing import components with local component products. Bushing is one of imported component that widely used on automotive application including motor strater. Bushing usually made of copper alloy such as brass, bronz or babbit in a solid form by casting or extrusion process. In this research powder metal technology is used to process Cu-Al powder to become slide bearing of motor starter. It is expected that powder metal process not only increasing local content in automotive parts but also providing better quality by increasing life time of bushing compared to ordinary one. Cu-Al metal powder was compacted at various pressure, i.e: 250 MPa, 350 MPa and 450 MPa, and then all specimens were sintered at different temperatures : 4000C, 5000C dan 6000C for 1 hour. After sintering specimens were air cooled to room temperature. After physical and mechanical test it can be deduced that bushing made by powder metallurgy method could increase its mechanical properties and as aresult improve its life time operation.